Desenvolvimento do processo de soldagem laser pulsado Nd:YAG para lâminas de 100 μm de espessura de AISI 316L - Ventrella, Vicente A. [UNESP] (2010)
Experimental investigations were carried out using a pulsed neodymium: yttrium aluminum garnet laser welding to examine the influence of the pulse energy in the AISI 316L thin foil welding with 100 μm thickness, employed to cover sensors that work in corrosive environment of the sugar and alcohol industry. The pulse energy was varied from 1, 5 to 3, 0 J at an increment of 0.25 J and 4 ms pulse duration. The specimens were laser-welded in an argon atmosphere. The welds were analyzed by macroscopic observations using optical microscopy and micro hardness. The results indicated that pulse energy control, in laser welding of thin foils, is of considerable importance for weld quality since it can generate discontinuities free weld joints. The geometric parameters of the welded joints like bead width, connection width and bead depth increased with the pulse energy increasing. The process showed very sensitive to porosity formation and gap between couple.